Lefamulin dosing optimization using population pharmacokinetic and pharmacokinetic/pharmacodynamic assessment in Chinese patients with community-acquired bacterial pneumonia - Bian, Xingchen; Li, Nanyang; Li, Yi; Zhu, Xu; Yu, Jicheng; Hu, Yingying; Yang, Haijing; Wei, Qiong; Wu, Xiaojie; Wang, Jingjing; Cao, Guoying; Wu, Jufang; et al. (Frontiers in Pharmacology, 2024)
Purpose Lefamulin is the first pleuromutilin antibiotic approved for the treatment of communityacquired bacterial pneumonia (CABP). However, the pharmacokinetic/pharmacodynamic (PK/PD) characteristics in Chinese CABP patients are not fully understood. This study aimed to evaluate its microbiological efficacy against Streptococcus pneumoniae and Staphylococcus aureus via PK/PD analysis.The population PK (PopPK) model, established with foreign data was validated using data from Chinese CABP patients. PK/PD analysis was conducted for the intravenous administration of 150 mg q12h for 1-h, 1.5-h and extended 2-h infusion. Oral administrations of 600 mg q12h were assessed, considering original and higher plasma protein binding.Lefamulin displayed similar PK characteristics in both Chinese and Western populations.The PopPK model effectively predicted lefamulin concentrations in Chinese CABP patients. Under the dosage regimen of 150 mg q12h via intravenous infusion for 1/1.5/2h, the probability of target attainments reached 98% at the minimum inhibitory concentration for both 90% Streptococcus pneumoniae and Staphylococcus aureus, considering both original and higher protein binding rates.It is advisable to extend the infusion duration from 1/1.5 h to 2 h to minimize the risk of adverse effects at the infusion site. Regardless of fasted or fed conditions, the PTAs for 600 mg q12h lefamulin via oral administration proved comparable to those for intravenous administration.This study proved that intravenous and oral administrations of lefamulin can reach preclinical PK/PD targets of Streptococcus pneumoniae and Staphylococcus aureus. These findings support the optimal use of lefamulin for the safe and effective treatment of Chinese CABP patients.